38‐2: Magnifying Viewer using Poly‐Si Thin‐Film Phototransistor and Liquid‐Crystal Micro‐Lens Array. Issue 1 (25th September 2020) - Kimura, Mutsumi; Kitajima, Shuhei; Li, Kun; Chu, Daping
Abstract : We have confirmed fundamental functions of a flatpanel imager using a poly‐Si thin‐film phototransistor and liquid‐crystal micro‐lens array. It is found that the electric current measured in the pixel on the white area is definitely larger than that on the black area. Particularly in this paper, it is clarified that the current difference for the lens‐on state is more obvious than that for the lens‐off state, and that for the polarizer‐on state is also more obvious than that for the polarizer‐off state. The experimental results are the same as what we expect and indicate the excellent effect of the liquid‐crystal micro‐lens array on the flatpanel imager using a poly‐Si thin‐film phototransistor. The magnifying viewer can be high‐resolutional by the flatpanel imager using the poly‐Si thin‐film phototransistor and liquid‐crystal micro‐lens array.